Viabilidade do uso de água residuária na agricultura irrigada na cultura do maxixe e aplicação como tema transversal no âmbito educacional - Souza, Elaine Barbosa de (2019)
Irrigation is the largest water consumer in the world, around 75% and we know that domestic effluents have essential nutrients for plant development. So the focus of the research was the use of domestic sewage water with initial treatment of stabilization ponds to supply the water needs of some crops, with a view to sustainability and rational use of water. Given the precarious availability of water in the world, this study sought to contribute to research in this field, emphasizing the reuse of water in irrigated agriculture, potentiating effective means for saving drinking water. The objective of this research was to evaluate the viability of the reuse of wastewater from a sewage treatment system by stabilization ponds in irrigated agriculture of the maxixe crop, aiming at the optimization of natural resources. The present research was carried out in an agricultural protected environment of the Department of Agronomic Engineering of the Federal University of Sergipe. The wastewater was collected weekly in the ETE of the Rosa Elze neighborhood, located in the Municipality of São Cristóvão / SE. The microbiological variables of the culture were determined by the Technological Research Institute of Sergipe (ITPS), the results obtained in the analyzes of the samples submitted from the three treatments - T1, T2 and T3, which met the established limits. With the results presented in this research, it is recommended the reuse of initially treated water from the stabilization pond, to the farmers, in up to 100% of the irrigation in the culture of the maxixe. In the educational project the research was applied in the field, the method used were the active teaching and learning methodologies in which the pedagogy of problematization was focused. In order to apply the Transversality in High School, a group of the 1st grade of the High School of the State School Professor Hamilton Alves Rocha was used, applying the methodology in the content separation of mixtures. According to the results, it was observed that the use of the active methodologies was relevant and quite productive, it was noticed the interest and learning in the discussions, debates and evaluations carried out among the researched ones.